1976
DOI: 10.1111/j.1399-3054.1976.tb03995.x
|View full text |Cite
|
Sign up to set email alerts
|

Salinity and the Hydraulic Conductance of Roots

Abstract: The effect of salinity on hydraulic conductance of intact roots of tomato (Lycopersicon esculentum Mill.) and sunflower (Helianthus annuus L.) was determined in split‐root experiments using salinized nutrient solutions. Experiments were conducted in controlled climate chambers under two or three relative humidity levels and four solution osmotic potential levels. The relationship between water flux through roots (Jv) and total water potential difference between the leaves and the root medium (Δψ) was linear, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
2

Year Published

1979
1979
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 17 publications
(25 reference statements)
2
21
2
Order By: Relevance
“…A strong linear relationship (r = 0.97) between EC of the nutrient solution and tomato plant water absorption has been demonstrated [170]. For other species, it has been suggested that root permeability decreased under salt stress and might explain the reduction of water uptake [64,152], but this explanation is not conclusive for tomato grown under 0-200 mM NaCl [158,162]. Tomato fruit has a very low transpiration rate and only around 15% of the water input comes via the xylem [90].…”
Section: Effect Of Electrical Conductivity Of the Nutrient Solution Omentioning
confidence: 84%
“…A strong linear relationship (r = 0.97) between EC of the nutrient solution and tomato plant water absorption has been demonstrated [170]. For other species, it has been suggested that root permeability decreased under salt stress and might explain the reduction of water uptake [64,152], but this explanation is not conclusive for tomato grown under 0-200 mM NaCl [158,162]. Tomato fruit has a very low transpiration rate and only around 15% of the water input comes via the xylem [90].…”
Section: Effect Of Electrical Conductivity Of the Nutrient Solution Omentioning
confidence: 84%
“…was observed in melon roots after 3 d NaCl supply. Reductions in root hydraulic conductivity, L p , of salinized plants have been shown in several reports (Shalhevet et al, 1976 ;Munns & Passioura, 1984 ;Evlagon et al, 1990), suggesting that the osmotic concentration had negative effects on L p . However, we previously reported (Carvajal et al, 1999) that NaCl produced a decrease in the L !…”
Section: mentioning
confidence: 99%
“…maritima leaves were consistent with the latter finding and showed that the effect of increasing salinity on cuticle thickness (1*6 times) was very close to that for the reduction in cuticular transpiration (1-5 times). A significant increase (1'6 times) in cuticular resistance may play a part in decreasing transpiration rates, a phenomenon frequently observed under saline conditions (Delf, 1912;Schratz, 1934;Uphof, 1940;Ashby and Beadle, 1957;Waisel, 1972;Kleinkopf, Wallace and Hartosock, 1976;Shalhevet et al, 1976;Siadat-Pour, 1978), and a decreased flux of water through the plant would significantly mitigate against excessive ion transport to the shoot.…”
Section: Cuticular Transpirationmentioning
confidence: 99%